2002
DOI: 10.1128/iai.70.12.6715-6725.2002
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Immunity Provides Optimal Protection against Both Mucosal and SystemicTrypanosoma cruziChallenges

Abstract: Chagas' disease results from infection with Trypanosoma cruzi, a protozoan parasite that establishes systemic intracellular infection after mucosal invasion. We hypothesized that ideal vaccines for mucosally invasive, intracellular pathogens like T. cruzi should induce mucosal type 2 immunity for optimal induction of protective secretory immunoglobulin A (IgA) and systemic type 1 immunity protective against intracellular replication. However, differential mucosal and systemic immune memory could be difficult t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
50
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 29 publications
7
50
0
3
Order By: Relevance
“…In addition to secreting IFN-␥, spleen cells from mice immunized with plasmids containing the clone 9 gene also produced NO, a potent inhibitor of T. cruzi development in vivo (22,24,31,44). Our results are compatible with those of recent studies showing that a strong Th1, but not Th2, immune response can provide a high degree of systemic immunity against experimental T. cruzi infection in BALB/c mice (11,12,37). However, the precise role of these IFN-␥-secreting CD4 ϩ T cells in protective immunity remains to be determined.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to secreting IFN-␥, spleen cells from mice immunized with plasmids containing the clone 9 gene also produced NO, a potent inhibitor of T. cruzi development in vivo (22,24,31,44). Our results are compatible with those of recent studies showing that a strong Th1, but not Th2, immune response can provide a high degree of systemic immunity against experimental T. cruzi infection in BALB/c mice (11,12,37). However, the precise role of these IFN-␥-secreting CD4 ϩ T cells in protective immunity remains to be determined.…”
Section: Discussionsupporting
confidence: 82%
“…However, the precise role of these IFN-␥-secreting CD4 ϩ T cells in protective immunity remains to be determined. Until now, there has been no clear evidence that specific CD4 ϩ Th1 cells alone can provide protective immunity against T. cruzi infection (11,12,37). These cells most likely have to interact with other T-and B-cell subsets in order to provide optimal protection against systemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 plus anti-IFN-␥ induced type 2 polarized responses that failed to protect against systemic T. cruzi challenges (15). More recently, we extended these observations showing that despite the prediction that an ideal vaccine should induce optimal mucosal type 2 immunity protective against initial invasion in the relevant mucosal lymphoid tissue, type 1 polarized responses induced by intranasal vaccination were optimally pro-tective against both mucosal and systemic T. cruzi challenges (13).…”
mentioning
confidence: 48%
“…However, more sensitive parasite detection techniques have confirmed that parasites persist in tissues and correlated this persistence with tissue damage (31,32). Furthermore, it is well accepted that a T helper 1 (Th1) type of immune response is required for clearing the parasite from infected mice (18,28,33,38,42,49), while such a response has also been associated with the intensity of the pathology during the chronic phase in humans (1,16). All this controversy has interfered substantially with the development of immunotherapy and preventive vaccines as there is no clear agreement concerning whether the immune response should be stimulated (to eliminate the parasite) or inhibited (to avoid autoimmunity).…”
mentioning
confidence: 99%